Pengaruh Spiritual Support (Dzikir) terhadap Tingkat Kecemasan Pasien Penyakit Jantung Koroner di ICU RSI Sultan Agung Semarang - Fajrin Ziad Syahputra; Dwi Heppy Rochmawati (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Coronary heart disease is one of the major health problems that not only affects the physical condition of patients but also impacts their psychological state, particularly anxiety. Anxiety levels in patients with coronary heart disease usually increase when they are about to undergo invasive medical procedures such as Percutaneous Coronary Intervention (PCI). Anxiety can be influenced by several factors, including age, gender, educational level, and occupation. High levels of anxiety may worsen the patient’s clinical condition, making appropriate non-pharmacological interventions highly necessary to help reduce anxiety. This study aims to determine the effect of spiritual support in the form of dzikir on the anxiety levels of patients with coronary heart disease. The research design used was a true experimental design with a pretest-posttest control group design. The sample consisted of 30 respondents who were evenly divided into two groups: 15 respondents in the intervention group and 15 respondents in the control group. The sampling technique used was total sampling. The instrument for measuring anxiety was the Hamilton Anxiety Rating Scale (HARS). The results showed that providing spiritual support in the form of dzikir was effective in reducing patient anxiety, with a p-value of 0.001. In addition, there was a significant difference in post-therapy anxiety levels between the control and intervention groups, with a p-value of 0.019 (p < 0.05). These findings demonstrate that dzikir, as a form of spiritual support, can be used as a non-pharmacological intervention to reduce anxiety in patients with coronary heart disease. Thus, spiritual support can be an important component of nursing care for patients in the ICU.